ETNOLINGUISTIK LEKSIKON TUMBUHAN DALAM IDIOM BAHASA JERMAN - Tri Edliani Lestari (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2020)
The study entitled "Plant Lexicons Ethnolinguistic in German Idioms" and aims to explain the culture reflected in German idioms that use plant lexicons. This ethnolinguistic study is qualitative in design. The data source used in this study is the German idiom dictionary named Duden Redewendungen in 2012, while the data used in this study are sentences containing idioms that contained in the Duden Redewendungen dictionary in 2012. Reflection of culture in the results of research on German idioms which use this plant lexicon is divided into seven parts, namely independence, self-actualization, achievement, work skills, self-esteem, brotherhood, and finally the responsibility.